Levels of B2-Microglobulin and Association of ACE Gene I/D Polymorphism with Type 2 Diabetes Mellitus patients - Hussain, Nageen; Mahwish, Mahwish (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Background Diabetes mellitus is a metabolic ailment which is an outcome of defect in insulin secretion, insulin action, or both. The ACEgene systematizes Angiotensin Converting Enzyme (ACE) and is the most profoundly studied gene because of its crucial role in the renin-angiotensin system (RAS). The insertion/ deletion (I/D) of a 287bp long Alu repetitive sequence in intron 16 is responsible for three genotypes, DD and II homozygotes and ID heterozygotes.ACE levels differ in carriers with respect to their genotype; DD carriers have twice the levels of ACE than that found in II genotype individuals. The main purpose of this study is to investigate the association ofACE gene I/Dpolymorphism in Pakistani Type 2 Diabetes Mellitus (T2DM) patients primarily from Lahore. Methods:Hundred patients (T2DM) and fifty healthy controls were enrolled in this study. The ACE I/D polymorphism, located in intron 16, was analyzed by a triple primer method called nested-PCR and subsequently the results were analyzed by gel electrophoresis.Urine samples were also collected from patients suffering from diabetic nephropathy for the determination of beta-2 microglobulin. Results: The frequency of ACE genotypes DD, ID and II among the patients with type 2 diabetes mellitus was found to be 76%, 10%, 14% whereas in control subjects, 38% , 4% , 8% respectively. Other clinical parameters like blood sugar level and body mass index were also evaluated to find an association with genotype. The findings showed a non-significant association of ACE genotype with Blood Sugar Level (BSL) and Body Mass Index (BMI).Of the hundred T2DM patients enrolled in the study ten (10%) were of diabetic nephropathy. Beta-2-microglobulin was measured in the urine of these patients as well as healthy controls. A significant association between B2-microglobulin and T2DM was found by Fischers exact test. Serum creatinine values were noted and correlation was found. The results showed a positive correlation but non-significant between creatinine and beta-2-microglobulin. Conclusion:In the present study, no significant association was found between ACE gene I/D polymorphism and T2DM. Gender of the T2DM patients showed null effect on genotype. Other clinical parameters like blood sugar level and body mass index also revealed a non-significant association with the ACE gene genotype.